The Impact of Human Capital on Employee Performance in the Automotive Parts Industry in Thailand - Worrakulrattana, Pattaraporn; Luekitinan, Wannapa; Soonthonsmai, Vuttichat (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2021)
This research is aimed at studying the impact of human capital on employee performance in Thailand’s vehicle parts industry. The sampling group utilized in this research is production supervisors in vehicle parts industry in Thailand with the number of 390 people. To select this sampling group is processed by means of stratified random sampling method based on the proportion of sampling population. Research tools combine questionnaire with 202 samplers responding. With analysis under structural equation modeling (SEM), it is found that human capital has a direct and positive impact on employee performance in terms of working effectiveness and working behaviour. In addition, the variance of working behaviour is explained by human capital with a percentage of 97%.